APPLICATION OF CO-CREATION EXPERIENCE IN CREATING CONSUMER SATISFACTION WITH HEALTH PERCEPTIONS AS A STIMULATING VARIABLE (STUDY OF MILLENIAL CONSUMERS ON MSMES IN MATARAM CITY) - Suardana, I Made (SULTANIST: Jurnal Manajemen dan Keuangan, 2022)
This study aims to determine the significance of co-creation experience on millennial consumer satisfaction for MSMEs in Mataram City with health perceptions (application of health protocols by the government) as a stimulant. The number of respondents was 141 students, the analysis used in this study is RMA and was equipped with the entire measurement process, namely, validity and reliability tests and classical assumption tests. Hypothesis testing was carried out through significance tests (t and F) and other parameters. Based on the t test, it was found that the application of co-creation experience partially had a significant effect and the role of health perception as a stimulant. The level of influence of these two variables is quite strong, which is 72.10%. There was a finding that the level of influence from the application of co-creation experience was partially low, so it was tried to build a model by taking into account the related variables, it was found that the level of influence was 68.00%. This is due to the nature of the perception of health as an absolute requirement of legislation carried out by MSMEs in the city of Mataram. This means that health protocols are absolute. This finding states that the co-creation experience can make it a priority in achieving customer satisfaction, especially in implementing it which only requires dialogue, openness and access for consumers to the company. it was found that the level of influence was 68.00%. This is due to the nature of the perception of health as an absolute requirement of legislation carried out by MSMEs in the city of Mataram. This means that health protocols are absolute. This finding states that the co-creation experience can make it a priority in achieving customer satisfaction, especially in implementing it which only requires dialogue, openness and access for consumers to the company. it was found that the level of influence was 68.00%. This is due to the nature of the perception of health as an absolute requirement of legislation that MSMEs carry out in Mataram. This means that health protocols are absolute. This finding states that the co-creation experience can make it a priority in achieving customer satisfaction, especially in implementing it which only requires dialogue, openness and access for consumers to the company.